Determinan Kejadian Ca Serviks di RSUD dr. Doris Sylvanus Kota Palangka Raya - Erina Eka Hatini; Kunita Maerani; Itma Annah; Vissia Didin Ardiyanid (Optimal Midwife Journal, 2025)
Cervical cancer is a malignancy that occurs in the cervix due to abnormal growth of cervical epithelial tissue. This study aims to determine the risk factors associated with the incidence of cervical cancer at RSUD dr. Doris Sylvanus Palangka Raya City. The research method used was descriptive quantitative with case control design and retrospective approach. The sample consisted of 80 respondents who were divided into 40 case groups (suffering from cervical cancer) and 40 control groups (not suffering from cervical cancer). Primary data were used in this study and analyzed univariately and bivariately using the chi-square test. The results of univariate analysis showed that the majority of respondents had HPV (53.8%), were >35 years old (60.0%), had parity >3 times (58.8%), married at the age of <20 years (57.6%), had a history of marriage >1 time (55.0%), smoked (56.3%), had a family history of cervical cancer (61.3%), and used hormonal contraception (60.0%). Bivariate analysis showed a significant association between the incidence of cervical cancer and HPV factors (p=0.0001), age (p=0.0001), number of parities (p=0.0001), age at first marriage (p=0.0001), history of marriage (p=0.0001), smoking (p=0.0001), family history (p=0.0001), and use of hormonal contraceptives (p=0.0001). In conclusion, the main risk factors for cervical cancer are HPV infection, age >35 years, parity >3 times, age at marriage <20 years, history of marriage >1 time, smoking habit, family history of cervical cancer, and use of hormonal contraceptives.